The Friedman Legacy : a Tribute to William and Elizebeth Friedman - The Center for Cryptologic History, Edited (Center for Cryptologic History, NSA, 2006)
A collection of six lectures on cryptology given by William Friedman, along with articles about William and his wife, Elizebeth.